Python Basics : Coding Club Level 1 - Chris Roffey (United Kingdom CAMBRIDGE UNIVERSITY PRESS, 2013)
A unique series that provides a framework for teaching coding skills. Learn the basics of coding quickly! This lively book is an introduction to the world of coding and to Python 3 - a fantastic language to start coding with. Young programmers will learn how to code and customise several fun applications including their own Magic8Ball and an Etch A Sketch(R) game. The fun challenges and Quick Quizzes help to consolidate new skills and the companion web site provides the full source code for all the projects and challenges as well as help for readers.
Keywords: IGCSE - ICT + Non Fiction -- IGCSE - ICT + Non Fiction